Tree species diversity predicts aboveground carbon storage through functional diversity and functional dominance in the dry evergreen Afromontane forest of Hararghe highland, Southeast Ethiopia - Wondimu, Mengistu Teshome; Nigussie, Zebene Asfaw; Yusuf, Muktar Mohammed (Ecological processes, 2021)
BACKGROUND: Regarding the most important ecological challenges, scientists are increasingly debating the relationship between biodiversity and ecosystem function. Despite this, several experimental and theoretical researches have shown inconsistencies in biodiversity and ecosystem function relationships, supporting either the niche complementarity or selection effect hypothesis. The relationship between species diversity, functional diversity, and aboveground biomass carbon was investigated in this study employing standing aboveground carbon (AGC) stock as a proxy measure for ecosystem function. We hypothesized that (i) effects of diversity on AGC can be transmitted through functional diversity and functional dominance; (ii) effects of diversity on AGC would be greater for functional dominance than functional diversity; and (iii) effects of functional diversity and functional dominance on carbon stock varied with metrics and functional traits. Community-weighted means (CWM) of functional traits (wood density, specific leaf area, and maximum plant height) were calculated to assess functional dominance (selection effects). As for functional diversity (complementarity effects), multi-trait functional diversity (selection effects) indices were computed. We tested the first hypothesis using structural equation modeling. For the second hypothesis, the effects of environmental variables such as slope, aspect, and elevation were tested first, and separate linear mixed-effects models were fitted afterward for functional diversity, functional dominance, and the two together. RESULTS: Results revealed that slope had a significant effect on aboveground carbon storage. Functional diversity and functional dominance were significant predictors of the aboveground carbon storage (22.4%) in the dry evergreen Afromontane forest. The effects of species richness on aboveground carbon storage were mediated by functional diversity and functional dominance of species. This shows that both the selection effects and the niche complementarity are important for aboveground carbon storage prediction. However, the functional diversity effects (niche complementarity) were greater than functional dominance effects (selection effects). CONCLUSIONS: Linking diversity and biodiversity components to aboveground carbon provides better insights into the mechanisms that explain variation in aboveground carbon storage in natural forests, which may help improve the prediction of ecosystem functions.